Buckling Of Axially Compressed Cones With Imperfect Axial Length - Mahidan, Fairuz Mardhiah; Ifayefunmi, Olawale Friday (Brazilian Association of Computational Mechanics, 2020)
The paper considers the effect of imperfect length on the buckling behavior of axially compressed mild steel truncated cone. Three types of initial geometric imperfections with different number of waves along the compressed edge are analyzed, and they are: (i) sinusoidal waves, (ii) triangular waves, and (iii) square waves. A validation of experimental data from previous study and further numerical calculations are provided in this paper. A good repeatability of experimental data was revealed through the test results with only 0% to 7% of error. Numerical simulations were carried out using ABAQUS FE code. It is shown that the buckling load of the cone is differently affected by the shape and amplitude of the imperfection. Apparently, the buckling loads of analyzed cones are less sensitive when imperfection shape is triangular as compared to other imperfection shapes. Furthermore, the effect of number of waves on buckling load of axially compressed cones was investigated for the above three cases. Results indicate that the influence of number of waves on the load carrying capacity of the cone is less significant.